Immune cell infiltration as a biomarker for the diagnosis and prognosis of digestive system cancer. Issue 12 (2nd November 2019) - Yang, Sheng; Liu, Tong; Cheng, Yanping; Bai, Yunfei; Liang, Geyu
Abstract: The digestive system cancers are aggressive cancers with the highest mortality worldwide. In this study, we undertook a systematic investigation of the tumor immune microenvironment to identify diagnostic and prognostic biomarkers. The fraction of 22 immune cell types of patients were estimated using CIBERSORT. The least absolute shrinkage and selection operator (LASSO) analysis was carried out to identify important immune predictors. By comparing immune cell compositions in 801 tumor samples and 46 normal samples, we constructed the diagnostic immune score (DIS), showing high specificity and sensitivity in the training (area under the receiver operating characteristic curve [AUC] = 0.929), validation (AUC = 0.935), and different cancer type cohorts (AUC > 0.70 for all). We also established the prognostic immune score (PIS), which was an effective prognostic factor for relapse‐free survival in training, validation, and entire cohorts ( P  < .05). In addition, PIS provided a higher net benefit than TNM stage. A composite nomogram was built based on PIS and patients' clinical information with well‐fitted calibration curves (c‐index = 0.84). We further used other cohorts from Gene Expression Omnibus databases and obtained similar results, confirming the reliability and validity of the DIS and PIS. In addition, the unsupervised clustering analysis using immune cell proportions revealed 6 immune subtypes, suggesting that the immune types defined as having relatively high levels of M0 or/and M1 macrophages were the high‐risk subtypes of relapse. In conclusion, this study comprehensively analyzed the tumor immune microenvironment and identified DIS and PIS for digestive system cancers. Abstract : Our study comprehensively analyzed the utility of consideration of immune cells in the diagnosis and prognosis of digestive system cancers. The diagnostic immune score and prognostic immune score signature might serve as biomarkers for early diagnosis and predicting survival.